ANALISIS PORTOFOLIO DENGAN MENGGUNAKAN MODEL CAPM DAN APT UNTUK MEMPREDIKSI RETURN SAHAM LQ 45 DI BEI - Ita Fionita (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
The objective of the research is to analyze portfolio with Capital Asset Pricing Model (CAPM)and Arbitrage Pricing Theory (APT) to predict Stock Return of LQ 45 at Indonenesia Stock Exchange(BEI). This research uses simple linier regression analysis method for CAPM model and double linierregression analysis method for APT model. The independent variable in this research is LQ 45Stocks while the dependent variables are market risk premium, exchange, SBI, inflation and PDB.The analysis with CAPM and APT model is used to know the optimum portfolio return, whileIndex Jansen is used to measure the portfolio performance. Further, t test is used to know thedifference between CAPM and APT model. The sampling in this research is 31 companies withcertain criteria such as 1) A listed companies at LQ 45 stock at BEI, 2) Listed companies at LQ 45stock which are actively traded continuously from January 2009 to December 2010.